Improving EFL Learners’ Affective Skills Through the Use of Digital Game-Based Learning - Sri Wahyuni; Irawan, Nico; Ghofur, Abd; Pramujiono, Agung (Universitas Nahdatul Ulama Surabaya, 2025)
This research explores how digital game-based learning models work in EFL classrooms to develop affective competencies among learners and evaluates their effectiveness. The research also investigates the obstacles that emerged during its execution. The main objective of the game-based intervention was to develop affective competencies among students during their English language learning process. The research used classroom action research to study 36 high school students in Surabaya through interviews and questionnaires. The research shows that digital games in classroom teaching boost student affective engagement while making learning more enjoyable and motivating. The research indicates that game selection remains challenging because it requires matching games to instructional targets, and teachers need specialized training to execute the approach effectively. The research findings offer essential knowledge to educational institutions and teachers about digital games as tools to enhance emotional student involvement in language education and improve academic quality.